(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In article functions of characters in late prose of O. Bokeev are considered. Stories «Chertov Bridge», «Snow Girl» and the novel «Ataukere» are subjected to the problem analysis. In these works «the spiritual being» of the modern person is investigated. It is proved that in these compositions a main goal of an author’s position was the image of spirituality of the human person, a layer of «own atmosphere» of the person who reveals moral and philosophical aspect of the point of view of the author. Poetic function of use of expression «the naked person» is revealed. The attention to such concepts as spiritual nakedness and spiritual exinanition is paid. As spiritual degradation of the person the thought of human «nakedness», contrary to it is allocated, spiritual enrichment is characterized as desire «to dress» «nakedness». The sense of the contrast of characters of heroes, heroes antipodes is studied. The moral and philosophical aspect assuming need of close attention to spirituality of the person and his environment comes to light.